Kapasitas Organisasi Disperindag ESDM Kabupaten Garut dalam Mengembangkan Sentra Industri Kulit Sukaregang - Nazeeya, Nadia Tiana; Utami, Sawitri Budi (PREDIKSI : Jurnal Administrasi dan Kebijakan, 2024)
The study discussed the organizational capacity of the Industry, Trade, Energy and Mineral Resource Office of Garut Regency in developing Sukaregang Leather Industry Cluster. In the midst of efforts to develop it, problems associated with infrastructure, community’s potential, and the government’s role were encountered. The study used qualitative methods with data obtained from interviews, observations and secondary sources. According to Hall et al. (2003)’s organizational capacity, it was discovered that if the capacity was examined by considering each aspect as a single entity, the Industry, Trade, Energy and Mineral Resource Office was not yet equipped with the capacity to develop the industry cluster. However, if the emphasis on the interrelation between each aspect was taken into account, it could be considered that the Industry, Trade, Energy and Mineral Resource Office tried to compensate for the lack of capacity in some aspects by increasing the capacity in other aspects. It did not yet have adequate financial, human resource and infrastructure capacity. However, the relationship and network capacity and the planning and development capacity could minimize the impact of the lack of capacities mentioned, thus making it possible for the Industry, Trade, Energy and Mineral Resource Office to implement their programs accordingly.